Experimental and Numerical Study on the Permeation Grouting Diffusion Mechanism considering Filtration Effects - Guangxuan Zhu; Qingsong Zhang; Rentai Liu; Jiwen Bai; Wei Li; Xiao Feng (Geofluids)
Permeation grouting estimation is important for the design of grouting engineering. Filtration effects and rheological behavior play a key role in permeation grouting diffusion of cement-based grouts. To better understand the effect of filtration and grout rheological behavior on the grouting diffusion mechanism, one-dimensional permeation grout injections in sand columns under constant flow rate were performed by a self-developed experimental procedure. Experimental results showed that there were dramatic variations in rheological parameters and porosity along the diffusion distance. However, the rheological parameters changed slightly with time for each position. Based on the experimental results, a numerical model considering the filtration effect and grout rheological behavior was established to describe the mechanism of grout flow in porous media. In addition, numerical solutions from the proposed model are compared with the experimental results. The comparative results showed that the proposed numerical method can match the laboratory tests well. Finally, the effects of the grout flow velocity and the water/cement ratio of the grout on the diffusion mechanism are also discussed.